2019
DOI: 10.1093/jb/mvz010
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of cytochrome P450 1232A24 and 1232F1 from Arthrobacter sp. and their role in the metabolic pathway of papaverine

Abstract: Cytochrome P450 monooxygenases (P450s) play crucial roles in the cell metabolism and provide an unsurpassed diversity of catalysed reactions. Here, we report the identification and biochemical characterization of two P450s from Arthrobacter sp., a Gram-positive organism known to degrade the opium alkaloid papaverine. Combining phylogenetic and genomic analysis suggested physiological roles for P450s in metabolism and revealed potential gene clusters with redox partners facilitating the reconstitution of the P4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…[98] Several recombinant enzymes were established for the preparative synthesis of these human demethylation metabolites. [99][100][101][102] The question remains why the products 17 and 19 were yet unknown as human metabolites of 4, although they appeared as major products of the P450 3A4 biocatalysis in this study. The benzylic position 10 of 4 is readily oxidised [103] and N-oxidation is a frequent transformation carried out by human P450 3A4.…”
Section: Substratementioning
confidence: 77%
See 3 more Smart Citations
“…[98] Several recombinant enzymes were established for the preparative synthesis of these human demethylation metabolites. [99][100][101][102] The question remains why the products 17 and 19 were yet unknown as human metabolites of 4, although they appeared as major products of the P450 3A4 biocatalysis in this study. The benzylic position 10 of 4 is readily oxidised [103] and N-oxidation is a frequent transformation carried out by human P450 3A4.…”
Section: Substratementioning
confidence: 77%
“…GC-MS confirmed the mass and the HSQC spectrum provided 13 C shifts of the product. No literature data could be found as a reference for 5hydroxypiperitone in research databases trans-6-hydroxypiperitone ( (6), 135 (12), 126 (59), 111 (35), 98 (100), 69 (41), 55 (18), 41 (29). By comparing to literature 1 H NMR data of both trans-and cis-6-hydroxypiperitone isomers, which show different chemical shifts due to the hydroxyl group sitting either in a pseudoaxial (trans to isopropyl) or -equatorial (cis to isopropyl) position, the formed product structure was suggested to be trans-6-hydroxypiperitone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cindoxin reductase displays strong similarity to NADPH-dependent ferredoxin reductases, and cindoxin reductase is replaced by Escherichia coli flavodoxin reductase. Klenk et al [ 128 ] reported two novel cyt P450s in Arthrobacter sp. , and they proposed the potential cluster in the genome including two cyt P450s and electron partners flavodoxin and flavodoxin reductase.…”
Section: Evolutionary Aspects Of Fnr-containing Nad(p)h-dependent Enz...mentioning
confidence: 99%